Effect of annealing temperature on the microstructure and morphology of BaZr0.45Ti0.55O3 thin films using the sol-gel method - Rahmi Dewi; Wahyu Akbar Illahi; Tengku Said Luqman Hussain Shahab (PSI-Aceh, 2022)
Abstrak. Ferroelektrik merupakan bahan elektronik khususnya dielektrik yang dapat diaplikasikan sebagai kapasitor. Ferroeletrik mempunyai kemampuan mengubah arah medan listrik internalnya dengan menggunakan medanl istrik yang sesuai. Barium titanat merupakan bahan yang bersifat ferroelektrik yang dapat didoping dengan bahan zirconium dan dapat dibuat dalam bentuk film tipis. Penambahan doping zirconium pada barium titanat akan meningkatkan konstanta dielektrik bahan. Pembuatan film tipis Barium Zirkoniun Titanat dengan komposisi (BaZr0.45Ti0.55O3) telah berhasil dibuat dengan menggunakan metode sol-gel. Variasi suhu annealing yaitu 600oC dan 650oC dengan waktu tahan 1 jam dan dikarakterisasi menggunakan difraksi sinar-X (XRD) dan scanning electron microscopy (SEM). Hasil karakterisasi XRD mendapatkan parameter kisi a = b = 3,97Ȧ danc = 4,25 Ȧ sehingga struktur kristalnya adalah tetragonal. Tingkat kekristalan semakin tinggi dengan bertambahnya suhu annealing yang ditandai dengan meningkatnya intensitas. Karakterisasi SEM menunjukkan pada suhu annealing 600oC ukuran butiran belum terlihat jelas sehingga tidak dapat ditentukan ukuran butirannya. Pada suhu 650oC ukuran butirannya dapat ditentukan dengan nilai ukuran butiran rata-ratanya adalah sekitar 134,5 nm. Abstract. Ferroelectric is an electronic material, the dielectric in particular, which can be applied as a capacitor. Ferroelectric is able to change the direction of its internal electric field by the use of a suitable electric field. Barium Titanate is a ferroelectric material which can be doped with zirconium and made in the form of a thin film. The addition of zirconium doping to Barium Titanate will increase the dielectric constant of the material. The making of Barium Zirconiun Titanate thin film with the composition (BaZr0,45Ti0,55O3) has been successfully prepared using the sol-gel method. The annealing temperature variations are 600oC and 650oC with a 1 hour holding time and characterized using X-ray diffraction (XRD) and scanning electron microscopy (SEM). The XRD characterization results obtain lattice parameters of a = b = 3.97 and c = 4.25 Ȧ, and thereby, the crystal structure is tetragonal. The crystallinity level is highly increasing with increased annealing temperature, indicated by increased intensity. SEM characterization shows that at annealing temperature of 600oC, the grain size is not clearly visible, so the grain size cannot be determined. At a temperature of 650oC, the grain size can be determined with the average grain size of about 134.5 nm.